APLIKASI RSS READER MENGGUNAKAN AJAX DAN JQUERY - Saputra, Rendi; Hamzah, Amir; Raharjo, Suwanto (Jurnal Script, 2013)
ABSTRACTÂ The development of rapid information technology makes the need for information / news more so urgently needed. To open a blog or website, Internet users can also forget the address of your blog or website that he thought attractive, even they also find it quite difficult when I have to look up the address they want our site Google. RSS (Really Simple Syndication) is an application that can be used by internet users to overcome the difficulties that arise as the site address or a search process to find out the latest information. In this thesis made the application RSS Reader using ajax and jQuery. The process of making this system begins with making the system analysis, system design that includes context diagram, DAD, and then making the program. While the database used is MySQL and the PHP programming language danJQuery. The application system can help to admin / user bias get information such as news headlines right from your blog / website updates.Â Keywords: RSS, Feeds, JQuery, Javascript,